Determination of the crop coefficient and biometric parameters based on images captured with drone, drainage lysimeters and indirect methods for the cultivation of potato solanum spp - León Ruiz, Juan (2016)
In order to determine the cultivation coefficients for the water requirement and the influence on the biometric parameters using images captured with drone, drainage lysimeters and indirect methods for the cultivation of potato Solanumspp in Riobamba - Ecuador, the methods were compared: drainage, evaporation tank type A, FAO Penman Monteith formula, and drone-captured orthophotos. The study was carried out on the premises of the Experimental Irrigation Center of the Escuela Superior Politécnica de Chimborazo in the Riobamba canton, Chimborazo province. Three complete digital agrometeorological stations were used; 3 drainage lysimeters were installed. Tensiometers located in the root zone at 15 - 30 and 45 cm depth were used to measure soil moisture. For the implementation of the field research, a completely randomized block design with three treatments was used (T1 = application of the irrigation sheet measured with a lysimeter, T2 application of the irrigation sheet measured with tank type A, T3 application of the irrigation sheet calculated with formula) and three repetitions ending with an analysis of variance at 5%. Comparison of the cumulative evapotranspiration calculation for each day was achieved by the indicated methods. There were 4 overflights, taken every 30 days after planting. It is concluded that the Kc map obtained by remote detection presents a useful description of the evapotranspiratory process in the months studied, with a similarity between the characteristic curves for validation with the direct lysimeter method and reference values ​​found in the literature. Furthermore, there is agreement between the Kc values ​​presented by remote sensing and the development phases and physiological processes of the plant.